We Are The World : Dutch Pavilion - Biennale di Venezia. - Biennale di Venezia Venetië 2003; van Beers, Hans; Medina, Cuauhtémoc ([S.l.] : Artimo, 2003)
Amorales, Carlos ; Framis, Alicia ; Gaba, Meschac ; van Heeswijk, Jeanne ; van Lieshout, Erik
Biennale di Venezia, Dutch Pavilion, 15 juni - 2 november 2003
kunstcatalogus